Intratumoral Heterogeneity and Immune Response Indicators to Predict Overall Survival in a Retrospective Study of HER2-Borderline (IHC 2+) Breast Cancer Patients - Radziuviene, Gedmante; Rasmusson, Allan; Augulis, Renaldas; Grineviciute, Ruta Barbora; Zilenaite, Dovile; Laurinaviciene, Aida; Ostapenko, Valerijus; Laurinavicius, Arvydas (Frontiers in Oncology, 2021)
Breast cancer (BC) categorized as HER2 borderline (2+ by immunohistochemistry, IHC 2+) presents challenges for the testing, frequently obscured by intratumoral heterogeneity (ITH). This leads to difficulties in therapy decisions. We aimed to establish prognostic models of overall survival (OS) in these patients using hexagonal tiling (HexT) analytics of digital image analysis (DIA) data to take into account spatial aspects of ITH and tumor microenvironment (TME). In particular, we assessed the prognostic value of Immunogradient indicators at the tumor-stroma interface zone (IZ) as a feature of anti-tumor immune response. Surgical excision samples stained for ER, PR, Ki67, HER2 and CD8 from 275 patients with HER2 IHC 2+ invasive ductal BC were used in the study. DIA outputs were subsampled by HexT for ITH quantification and TME extraction for Immunogradient indicators. Multiple Cox regression revealed HER2 membrane completeness (HER2 MC) (HR: 0.18, p = 0.0007), its spatial entropy (HR: 0.37, p = 0.0341) and ER contrast (HR: 0.21, p = 0.0449) as independent predictors of better OS, with worse OS predicted by pT status (HR: 6.04, p = 0.0014) in HER2 non-amplified patients. In HER2-amplified patients, HER2 MC contrast (HR: 0.35, p = 0.0367) and CEP17 copy number (HR: 0.19, p = 0.0035) were independent predictors of better OS along with worse OS predicted by pN status (HR: 4.75, p = 0.0018). In the non-amplified tumors, three Immunogradient indicators provided independent prognostic value: CD8 density in the tumor aspect of IZ and CD8 center of mass were associated with better OS (HR: 0.23, p = 0.0079 and 0.14, p = 0.0014, respectively), and CD8 density variance along the tumor edge predicted worse OS (HR: 9.45, p = 0.0002). Combining these 3 computational indicators of the CD8 cell spatial distribution within the TME augmented prognostic stratification of the patients. In the HER2-amplified group, CD8 density in the tumor aspect of IZ was the only independent immune response feature to predict better OS (HR: 0.22, p = 0.0047). In conclusion, we present novel prognostic models, based on computational ITH and Immunogradient indicators of the IHC biomarkers, in HER2 IHC 2+ BC patients.